Relationship between power and knowledge in choosing a cesarean section: women's perspectives - Ana Paula de Lima Escobal; Ana Paula Müller de Andrade; Greice Carvalho de Matos; Patricia Haertel Giusti; Susana Cecagno; Lisie Alende Prates (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the reasons and motives that initiates the decision to choose a cesarean section, by describing the plots, power relationships, struggles, and systems of truths regarding this method of childbirth. Methods: a qualitative study, inserted into a poststructuralist perspective, and conducted in a city in southern Rio Grande do Sul state. The settings were a teaching hospital and home residences. Thirteen postpartum women who had a cesarean section participated. The analysis consisted of questions based on the information produced and articulated with Foucauldian theories. Results: two categories were developed: "I wanted a vaginal delivery, but it was a cesarean section", and, "Are you sure you want a vaginal delivery: paths and detours in the choice of cesarean section". Final Considerations: the study allowed us to identify problems in the choice for a cesarean section, which is associated with the circulation of "truths" that occur via discourses on society.